Pengaruh Intensitas Cahaya Lampu dan Intensitas Terang Layar Komputer Terhadap Produktivitas dalam Mengetik - Retno Indriartiningtias; Nia Budi Puspitasari; Trifandi Lasalewo (Performa: Media Ilmiah Teknik Industri, 2009)
In this recent time, almost all of jobs sectors using technology and computer for they activities. By using computers, they reach value added as efficiency, more faster, and validity. Using computers for a long time and for continuity activities, need work environment that support their produvtivity and their safety. Work environment such as lighting, the screen colour, the smels of room, etc are the factors that can influence activities’s productivity and quality. For that purposes, this paper research about the influence of intensity of lamp lighting and computer’s screen lighting to typing productivity. The experiment does with factorial design becouse they use two factors (intensity of lamp lighting and computer’s screen lighting ). Every factors have 3 levels (kualitative and kuantitative). The respons that want to know the typing productivity (word in 10 second) for each responden. The replication for the experiment is 3 for each treatment.From the result, there are no significant influence between intensity of lamp lighting, computer’s screen lighting and typing productivity.